ANALYSIS OF THE PREVALENCE OF RESPIRATORY SYMPTOMS IN PEOPLE PRACTITIONING PHYSICAL EXERCISE IN SANTOS - Gonzalez, Rosane Vianna; Braga, Alfésio Luís Ferreira; Pamplona, Ysabely de Aguiar Pontes; Enohi, Ricardo Toshio; de Carvalho, Valdilene Silva; Pinheiro, Micheli Darque; Lucena, Rogério Rocha; Martins, Lourdes Conceição (Seven Editora, 2025)
Objective. To analyze the prevalence of respiratory symptoms among exercise practitioners in Santos. Methods. A cross-sectional study was carried out through the registration of two self-administered questionnaires, one of which was a sociodemographic data questionnaire and the other a validated European Community Respiratory Health Survey (ECRHS) questionnaire for the evaluation of respiratory symptoms. Descriptive analyses of all variables, univariate and multiple logistic regression models to assess the risk of exposure, and analysis of spatial dynamics were performed. The significance level was 5%. Results. Exposure to moldy humidity (OR = 2.38; 95% CI: 1.31; 4.30), and higher education (OR = 6.96; 95% CI: 2.21; 21.45) were jointly significant factors for rhinitis. Regarding the responses to the ECRHS questionnaire, we can see that those who live in Ponta da Praia have a 2.43 (95% CI: 1.05; 5.64) times greater chance of having wheezing than those who live in other regions of Santos. The analysis of spatial dynamics shows a higher prevalence of respiratory symptoms in residents of Ponta da Praia. Conclusion. Exposure to air pollution plays an important role in respiratory symptoms such as rhinitis and wheezing among those who practice physical exercise in the region of the Rebouças Sports and Recreation Complex, Ponta da Praia, in the city of Santos.DOI: https://doi.org/10.56238/sevened2024.037-173